Baorangia duplicatopora (Boletaceae, Boletales), a new bolete from tropical China - Zhang, Xu; Liang, Zhi-Qun; Jiang, Shuai; Xu, Chang; Fu, Xin-Hua; Zeng, Nian-Kai (Phytotaxa, 2021)
Baorangia duplicatopora is described as a new species from Hainan Province, a tropical region of China. It is morphologically characterized by large to very large basidiomata with a dull rose red, rose pink to purplish red pileus, compound pores, pileus context near hymenophore and stipe context staining blue when injured, a red stipe, and cheilocystidia wider than those of other Baorangia species. Phylogenetic analyses of DNA sequences from part of the 28S gene, the nuc rDNA internal transcribed spacer (ITS) region, and part of the translation elongation factor 1-α gene (TEF1) also confirmed that B. duplicatopora forms an independent lineage within Baorangia. Detailed descriptions, color photographs of fresh basidiomata, and line drawings of microscopic features of the new species are presented. A key to species of Baorangia in the world is also provided.